Leveraging trade for women economic empowerment in the Pacific. - Asian Development Bank (Manila,Philippines Asian Development Bank, [2019])
It includes an analysis of how gender mainstreaming in Aid for Trade programs could catalyze greater donor support to help the region benefit from gender equitable and truly inclusive growth. In the Pacific, the labor force participation gap between men and women has narrowed, but women there are still less likely to be in work than men. To tap into the full potential of the female labor force in the region, much more needs to be done to boost women economic empowerment.
Keywords: Female workers; Entrepreneurs; Women politics; Electronic book